Discrete event simulation as a decision making tool for improving overall line efficiency - Yong, Wen Yao (2022)

(untitled)
This paper is about formulating a new decision-making framework that integrates discrete event simulation (DES) software to select the best alternative to improve a manufacturing system. Literature pertaining to decision-making tools, performance metrics and frameworks on decision-making as well as process improvement was reviewed. The advantages and limitations of techniques, strategies as well as frameworks adopted by recent researchers were ascertained. The review discovered that there is lack of comprehensive framework on deploying simulation tool as decision-making supporting instrument in process improvement. Vital features of decision-making and process improvement were explored through literature, and a new framework was designated by incorporating the vital features with rectified gaps found in recent works. To validate the feasibility of the proposed framework, it was then applied in a case study conducted at a box manufacturing factory in Sarawak, Malaysia, to improve the factory’s overall line efficiency (OLE). The framework provided guidelines in goal, objectives and decision criteria setting, constructing simulation models that was precise in reflecting the real system, identifying root causes, generating relevant solutions, experimenting solutions and selecting the best performing solutions with the aid of WITNESS 20 simulation software, analytic hierarchy process (AHP) as well as analysis of variance (ANOVA). As a result, it was predicted that the OLE will be improved to 89.61 % by enhancing the printer setup efficiency and operators’ troubleshooting skill. It was deduced that the new framework is more advantageous in selecting the best alternative in process improvement projects, compared to the conventional framework in various aspects.